2019
DOI: 10.1080/10717544.2019.1687613
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of zaleplon oral bioavailability using optimized self-nano emulsifying drug delivery systems and its effect on sleep quality among a sample of psychiatric patients

Abstract: 2019) Enhancement of zaleplon oral bioavailability using optimized self-nano emulsifying drug delivery systems and its effect on sleep quality among a sample of psychiatric patients, Drug Delivery, 26:1, 1243-1253, ABSTRACTThe aim of this work is to develop self-nano emulsifying drug delivery system (SNEDDS) to enhance the oral bioavailability of zaleplon (Zal) as a poorly water-soluble drug. Moreover, the bioavailability and the effect on the quality of sleep among a sample of psychiatric patients is to be as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…The excess liquid was then removed with absorbent paper. Prior to inspection with an acceleration voltage of 70 kV and magnification power of 150 KX 19, the sample was stained with a drop of an aqueous solution of phosphotungstic acid (2% w/v) for 3 min (2 % w/v) for 3 minutes [20] .…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…The excess liquid was then removed with absorbent paper. Prior to inspection with an acceleration voltage of 70 kV and magnification power of 150 KX 19, the sample was stained with a drop of an aqueous solution of phosphotungstic acid (2% w/v) for 3 min (2 % w/v) for 3 minutes [20] .…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…Extra fluid was then eliminated by with the aid of an absorbent paper, then observed by TEM (JEM 1010, JEOL Ltd, Tokyo, Japan) with an acceleration voltage of 70kV and magnification power of 150 KX. 29 , 30 …”
Section: Methodsmentioning
confidence: 99%
“…A small number of SEDDS-based products have already been successfully introduced into the pharmaceutical market, with none of them loading drugs for the treatment of neurological disorders. Until now, several in vivo assays using oral SEDDS have been carried out for neuropharmaceuticals brain targeting [ 4 , 6 , 23 , 24 , 25 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 70 ], but only a few in vivo pre-clinical studies have been reported for IN administration of neurotherapeutics loaded in SEDDS. In fact, only six studies were found that investigated the IN administration of neurotherapeutics loaded in SEDDS: clonazepam [ 45 ], diazepam [ 44 ], and perampanel [ 28 ] for epilepsy treatment; Bdph for glioblastoma treatment [ 4 ]; huperzine A [ 30 ] for Alzheimer’s disease; and naringin [ 5 ] as a neuroprotective for Alzheimer’s and Parkinson’s disease.…”
Section: Application Of Sedds In Brain Drug Delivery—pre-clinical Stu...mentioning
confidence: 99%